Allowing for Heterogeneity in the Consideration of Airport Access Modes: The Case of Bari Airport. Issue 8 (August 2019) - Bergantino, Angela S.; Capurso, Mauro; Dekker, Thijs; Hess, Stephane
Mode choice models traditionally assume that all objectively available alternatives are considered. This might not always be a reasonable assumption, even when the number of alternatives is limited. Consideration of alternatives, like many other aspects of the decision-making process, cannot be observed by the analyst, and can only be imperfectly measured. As part of a stated choice survey aimed at unveiling air passengers' preferences for access modes to Bari International Airport in Italy, we collected a wide set of indicators that either directly or indirectly measure respondents' consideration of the public transport alternatives. In our access mode choice model, consideration of public transport services was treated as a latent variable, and entered the utility function for this mode through a "discounting" factor. The proposed integrated choice and latent variable approach allows the analyst not only to overcome potential endogeneity and measurement error issues associated with the indicators, but also makes the model suitable for forecasting. As a result of accounting for consideration effects, we observed an improvement in fit that also held in a validation sample; moreover, the effects of policy changes aimed at improving the modal share of public transport were considerably reduced.